2016
DOI: 10.1017/s1478951516000468
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on one's own death: The existential questions that nurses face during end-of-life care

Abstract: Nurses in end-of-life care experience various emotions from patients related to things physical, spatial, and temporal. When nurses encounter these emotions as expressing a patient's suffering, they lead to challenges of balancing between different feelings in relation to patients, as both professional caregivers and fellow human beings. Nurses can experience growth both professionally and as human beings when caring for patients at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
3
8
0
6
Order By: Relevance
“…For example, evidence from the primary literature showed that nurses were often burdened by the professional expectation to manage the emotions of the grief and loss of the dying patients and their families as well as their own. 23 Inconsistencies in the participants' expectations of each other's roles were also found in the current study. In some cases, the views of doctors as to what their roles were differed to what the nurses perceived to be the role of the doctor.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, evidence from the primary literature showed that nurses were often burdened by the professional expectation to manage the emotions of the grief and loss of the dying patients and their families as well as their own. 23 Inconsistencies in the participants' expectations of each other's roles were also found in the current study. In some cases, the views of doctors as to what their roles were differed to what the nurses perceived to be the role of the doctor.…”
Section: Discussionsupporting
confidence: 69%
“…In line with the previous research, nurses in this study felt that they were professionally obliged to provide clinical care and, at the same time, to provide emotional support. For example, evidence from the primary literature showed that nurses were often burdened by the professional expectation to manage the emotions of the grief and loss of the dying patients and their families as well as their own 23 …”
Section: Discussionmentioning
confidence: 99%
“…This is partially because patients and families may be reluctant to make care transitions out of fear of losing the professional caregiver with whom they have developed a strong, trusting relationship (Sefcik et al, 2017) or from fear of being abandoned by their nurse (Back et al., 2009). Nurses, on the other hand, may also experience complex emotions or face existential questions about their personal identity, role as a professional caregiver and fellow human being, while caring for patients at the end‐of‐life (Karlsson et al., 2017). In prior research, assurances of non‐abandonment have been associated with expressions of satisfaction with clinician communication in serious illness (Sullivan et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study suggests that the technological obligations and moral/ethical concerns experienced by nurses regarding palliative care mostly cause them to suppress their actual feelings. In the previous studies, it was mentioned that nurses, who provided palliative care, learnt emotional management processes over time, recognized that acting as the institution expected of them (instead of actual emotions) might cause alienation of the self, tried to prevent grief by restricting the emotions, and this could conflict with their self-identities (29,33). In a study conducted on the factors affecting the emotional labor of the neonatal nurses, it was observed that the institutional support provided to nurses was not sufficient.…”
Section: Discussionmentioning
confidence: 99%